AN EXAMINATION OF PHILOSOPHICAL PROFILES IN PHYSICAL EDUCATION. A COMPARISON BETWEEN ROMANIA AND ITALY - Iosif SANDOR; Adrian PASCAN; Gabriela RUSU; Emanuele ISIDORI; Francesco TADDEI; Sabri KAYA (Cluj University Press, 2016)
Physical education is a discipline in which there are often few possibilities for teachers to develop critical thinking and reflexivity. This is due to prevalence, in the curricula of PE teachers, of technified teaching and learning models that do not help them develop as critical reflective practitioners. Within this consideration, and in order to stress the importance of philosophy as a means capable of developing critical thinking in physical education, we have administered to two groups of Romanian and Italian PE teachers a validated questionnaire aimed to detect their philosophical profiles on the basis of five paradigms. The result of our study has shown that, between the two groups of teachers, there exist differences relating to so-called Idealist and Positivist profile. In conclusion, the results and assumptions to explain them and emerging from the study need to be better explored, verified and analyzed by future researches based on a wider sample and focus group of scholars, teachers and respondent informants.